IMPROVING THE ECONOMIC MECHANISM OF DIVERSIFYING HOUSEHOLD INCOMES (American Journal of Interdisciplinary Research and Development, 2025)
This article delves into the issues surrounding the improvement of the economic mechanism for diversifying household incomes. The paper analyzes the evolution of theoretical approaches to income diversification, as well as its key principles and characteristics. The research also provides an in-depth look at the foreign experience of household income diversification, highlighting successful strategies from different countries and their effectiveness in expanding household incomes. The article aims to develop modern approaches to stabilizing and expanding household incomes in the context of global economic processes and digital transformation. Additionally, it offers specific recommendations and proposals for diversifying household incomes within the context of Uzbekistan.